Influence of field beans (Vicia faba L.) on yield and environmental footprint of following spring barley (Hordeum vulgare L.) crops - Umut Kartal; Colm Duffy; Sophie Saget; Frances Sandison; Andrew Christie; Cathy Hawes; Becky Howard; Roger Vickers; Dimitrios Savvas; David Styles; Pietro P. M. Iannetta (Plant and Soil, 2026)
Background and Aims The urgent need to reduce greenhouse gas emissions has increased interest in legume-based cropping systems. Among the various crop-legume species available, the cool-season species Vicia faba L. (cv. minor; field beans) has attracted significant interest. Assessment of the environmental impact reduction of field beans in a crop-sequence (rotation) is understudied. Methods Data from a long term (2009–2023) field bean experimental platform (the Centre for Sustainable Cropping, CSC; James Hutton Institute, Scotland, UK) were analysed using attributional life cycle assessment (aLCA). This focused on elaborating the impacts of a spring field bean to spring barley ( Hordeum vulgare L.) cropping sequence compared with a spring barley to spring barley cropping sequence. Results Field beans decreased the environmental impact of spring barley production in four of the five two-year crop-sequence periods, with mean impact reductions of approximately 25% across sequences. Spring barley grain yields tended to increase following field beans under drought conditions (2022). A combined index analysis indicated that humidity, maximum temperature, and previous field bean yields were the strongest determinants of spring barley production. Conclusions The integration of field beans to cereal-dominated rotations may be of interest to major industries who seek to improve value chain sustainability, whilst ensuring crop-sequence yields are climate-impact resilient.

Effects of mesoscale sea-surface temperature fronts on the marine atmospheric boundary layer - Eric D. Skyllingstad; Dean Vickers; Larry Mahrt; Roger Samelson (Boundary-Layer Meteorology, 2007)